Analysis of the Effect of Tax Planning, Deferred Tax Burden, and Company Size on Profit Management - Azqia Prafieta Hazh; Herry Krisnandi; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
Researchers want to re-evaluate data on different units and also the Covid-19 pandemic which has caused several sectors to experience a significant increase in the company's profits. To analyze the effect of tax planning, deferred tax expense, and company size on earnings management. In the basic perspective to understand the concept of earnings management, the organization has several agreements, for example an employment contract between the organization and its directors and an advance agreement between the organization and its bank. Where between the head and management need to expand the utility of each with the data they have. However, again Management has more data than heads, causing data to be unbalanced. In this study using purposive sampling technique, the number of sample data used in this study were 24 companies from the Indonesia Stock Exchange in the goods and consumption sub-sector. does not affect earnings management, Deferred tax burden has an effect on earnings management. With the conclusion that the greater the profit earned, the greater the tax to be imposed on the company, and vice versa. So the company should continue to do tax planning as an effort to minimize the company's taxable profit, because this is legal in the eyes of the State.